Frontispiece: Rationally designed modular drug delivery platform based on intracellular peptide self‐assembly (EXP2 2/2021). Issue 2 (30th October 2021) - An, Hong‐Wei; Mamuti, Muhetaerjiang; Wang, Xiaofeng; Yao, Haodong; Wang, Man‐Di; Zhao, Lina; Li, Li‐Li
Abstract : We fabricate a drug‐delivery system (MDS) through bioactivated in vivo self‐assembly (BIVA) nanotechnology. The percentage of solvent‐exposed surface area (%SASA) of MDS assembling modular, as well as its non‐covalent interaction between four other modules synergetically decide the stable conformation and modulate in situ assembly. Our MDS will benefit the further drug delivery to prolong the retention and accumulation.